PROSPECTS FOR THE DEVELOPMENT OF DOMESTIC TECHNOLOGY TOURISM BUSINESS MODELS IN THE CONTEXT OF CHINA'S AGEING POPULATION - Difei He; Suraphong Wacharajit (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The tourist industry is one of the economy's fastest-growing sectors today, and its significance in fostering cross-cultural understanding is generally acknowledged. The tourist industry is a significant employer and major contributor to the world economy, accounting for around 10% of GDP. Recent years have seen a surge in China's technologically-driven, alternative tourism trend. As a result, new tourism-related industries have increased and become significant employer. However, the tourism industry is currently experiencing a time of uncertainty, waiting, and stagnation due to the ongoing COVID-19 Pandemic. In addition, the international tourism industry has had "negative growth" since late 2019. Based on these challenges, this paper analyzes the current situation of the domestic senior tourist industry. Using self-administered questionnaires, researchers analyzed and researched the aforementioned factors and how they affect people's decision-making. Findings indicate that individual characteristics such as age and health status, annual income, education level, and leisure time have an effect, as do more general criteria such as location, family composition, and the current domestic tourism market. This paper makes several suggestions for future planning in domestic senior tourism market research, business model research, travel psychology analysis, and travel technology penetration to provide a realistic demand for senior tourism, explore the many areas of tourism planning, improve, and find new ways to innovate. In addition, they have researched the old travel market in the United States. This has a positive impact on the expansion of the senior tourist market.